Rodent pests of upland and lowland rice at a derived savanna site in Nigeria - Singh, B.N.; Asimalowo, A.A.; Ayodele, A.I. (1998)
Rodents are one of the major pests damaging the rice crop in Nigeria. Their population, damage, and species variation were monitored in upland, rainfed, and irrigated lowland areas in the 1994-95 dry and wet seasons. These fields were located at different sites within the experimental farm at IITA, Ibadan. The location represents a derived savanna agroecological zone, with an average bimodal rainfall of 1,400 mm.